Emotional reactions in the unemployed during economic recession in Greece: construction of a self- report emotional scale for use in unemployment (Nottingham Emotional Scale: NEScale) - Karaoulani, Ioanna (2019)
The function of emotions, especially the basic emotions, signpost individual's psychological resilience that refers to effective coping and adaptation to stressful situations and alert us for challenges that we must adequately address to sustain well-being. Precarious employment of white collar workers and long term unemployment can result in mental health problems while the distinctiveness of rural-urban unemployment highlights specific problems. The current literature does not offer measures that are designed to assess discrete emotions in relation to unemployment. Under that perspective, a new scale was devised. “Nottingham Emotional Scale (NEScale)” is a Likert scale self-report measure including 24 items that reflect three subscales, “Positive”, “Negative” and “Trauma and Stress-related”. Item generation was based on qualitative accounts, theory, and expert review. The scale has good internal consistency (N=2201) and two, four and six-week test-retest reliability indicated that the scores were stable over time. The validity of the scale is related to Brief Cope and Depression, Anxiety, Stress Scales (DASS-42), which assess related constructs. In terms of discriminant validity, the scale proved to be different from Satisfaction with Life Scale (SWLS) and Subjective Happiness Scale (SHS). NEScale scores were strong predictors of emotional health in employment and unemployment and pinpointed a difference in emotion between the employed and unemployed participants, with the employed scoring significantly higher on the “Positive” and the unemployed scoring higher on the “Negative” and “Trauma and Stress-related”. A strength of this project is that addresses a gap identified in the research literature; it presents a new emotional scale that does not assess only broad dimensions of affect (positivity and negativity), but it is sensitive to emotions that can be used as a parameter for the diagnosis, early identification and treatment of post-traumatic stress disorder (PTSD).